2021
DOI: 10.1257/pol.20190414
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of the 1930s HOLC “Redlining” Maps

Abstract: This study uses a boundary design and propensity score methods to study the effects of the 1930s-era Home Owners Loan Corporation (HOLC) “redlining” maps on the long-run trajectories of urban neighborhoods. The maps led to reduced home ownership rates, house values, and rents and increased racial segregation in later decades. A comparison on either side of a city-level population cutoff that determined whether maps were drawn finds broadly similar conclusions. These results suggest the HOLC maps had meaningful… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
170
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 145 publications
(186 citation statements)
references
References 57 publications
(57 reference statements)
4
170
0
Order By: Relevance
“…as redlining, was an obstacle to upward mobility through the denial of loans to credit-worthy applicants who lived in predominately Black neighborhoods and thus preventing people of color from moving into middle-class or upperclass communities. 32 Areas with a history of redlining are associated with increased health risks, 33 such as later stage cancer diagnosis, 34 even if the neighborhood economic status has risen. In addition, one study found that redlined neighborhoods have 60% higher breast cancer mortality compared with other neighborhoods.…”
Section: Mortalitymentioning
confidence: 99%
See 1 more Smart Citation
“…as redlining, was an obstacle to upward mobility through the denial of loans to credit-worthy applicants who lived in predominately Black neighborhoods and thus preventing people of color from moving into middle-class or upperclass communities. 32 Areas with a history of redlining are associated with increased health risks, 33 such as later stage cancer diagnosis, 34 even if the neighborhood economic status has risen. In addition, one study found that redlined neighborhoods have 60% higher breast cancer mortality compared with other neighborhoods.…”
Section: Mortalitymentioning
confidence: 99%
“…Although a small fraction of the variation in cancer mortality can be attributed to genetics differences, the majority of the Black‐White disparity is due to variations in SES and access to care because of decades of structural racism 5,6 . For instance, historically legal lending discrimination, known as redlining, was an obstacle to upward mobility through the denial of loans to credit‐worthy applicants who lived in predominately Black neighborhoods and thus preventing people of color from moving into middle‐class or upper‐class communities 32 . Areas with a history of redlining are associated with increased health risks, 33 such as later stage cancer diagnosis, 34 even if the neighborhood economic status has risen.…”
Section: Select Findingsmentioning
confidence: 99%
“…The purported mechanism behind these findings is that the HOLC maps served as a major source of information for private lenders, the HOLC, and the FHA in restricting the geographic scope of their mortgage activity. (Jackson 1985, Cohen 1990, Massey and Denton 1993, Sugrue 1996, Woods 2012, Baradaran 2017, Rothstein 2017, Faber 2020, Aaronson, Hartley, and Mazumder 2021.…”
Section: Introductionmentioning
confidence: 99%
“…“A” ratings were assigned to affluent White neighborhoods, while D ratings were assigned to neighborhoods that had a greater share of Black, lower class, or immigrant residents. Virtually all black families lived in D rated areas [ 2 , 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…HOLC maps reflected pervasive racism in the housing sector prevalent long before the maps were drawn [ 1 , 3 ], but HOLC took to an unprecedented scale the use of data to facilitate and justify racist appraisal and underwriting practices, thereby formalizing and legitimizing discrimination in the real estate sector and housing policy for subsequent decades [ 1 ]. The maps HOLC drew were shared in the real estate sector, notably with the Federal Housing Administration, which drew their own neighborhood maps that influenced the provision of mortgage insurance [ 2 , 4 ]. Billions of federally guaranteed real estate loans were then channeled into building primarily white affluent neighborhoods, limiting investment in minority neighborhoods, limiting access to homeownership for persons of color, and increasing racial residential segregation [ 1 ].…”
Section: Introductionmentioning
confidence: 99%